Ki67 expression at Kasai portoenterostomy as a prognostic factor in patients with biliary atresia. Issue 5 (16th June 2020) - Yoshii, D.; Inomata, Y.; Komohara, Y.; Shimata, K.; Honda, M.; Hayashida, S.; Oya, Y.; Yamamoto, H.; Yamamoto, H.; Sugawara, Y.; Hibi, T.
Abstract : Background: Biliary atresia is a rare paediatric biliary obliteration disease with unknown aetiology, and is the most common indication for paediatric liver transplantation (LT). However, no consensus for predicting Kasai portoenterostomy (KP) outcomes using liver histological findings exists. Ki67 is a popular biomarker for measuring and monitoring cellular proliferation. Methods: Ki67 (clone, MIB‐1) liver parenchyma expression was measured by immunohistochemical staining of samples from living donors and patients with biliary atresia to assess its value in predicting outcomes after KP. Results: Of 35 children with biliary atresia, 13 were native liver survivors (NLS), 17 were non‐NLS, and five had primary LT. The median proportion of Ki67 immunostained areas in donors and patients with biliary atresia at KP was 0·06 and 0·99 per cent respectively. Univariable analysis identified a high proportion of Ki67 areas, high Ki67 cell numbers and high Ki67‐positive/leucocyte common antigen‐positive cell numbers at KP as significant predictors of poor native liver survival after KP (hazard ratio 9·29, 3·37 and 12·17 respectively). The proportion of Ki67 areas in the non‐NLS group was significantly higher than that in the NLS group (1·29 versus 0·72 per cent respectively; P = 0·001), and then decreased at LT (0·32 per cent versus 1·29 per cent at KP; P < 0·001). Conclusion: This study has demonstrated the clinical data and time course of Ki67 expression in patients with biliary atresia. High Ki67 expression at KP may be an important predictor of native liver survival following the procedure. Abstract : No consensus exists for predicting outcomes after Kasai portoenterostomy (KP) using liver histological findings. Ki67 (clone, MIB‐1) expression in liver parenchyma was measured by means of immunohistochemical staining of samples from five living donors and 35 patients with biliary atresia to assess its value in predicting KP outcomes. Univariable analysis identified high expression of Ki67 at the time of KP as a significant predictor of poor native liver survival after the procedure. Ki67 a potential marker for liver survival after Kasai portoenterostomy Abstract : Antecedentes: La atresia biliar ( biliary atresia, BA) es una enfermedad pediátrica rara que consiste en una obstrucción biliar de etiología desconocida, y es la indicación pediátrica más frecuente de trasplante hepático ( liver transplantation, LT). Sin embargo, no existe consenso para predecir los resultados de la portoenterostomía de Kasai (Kasai portoenterostomy, KP) en base a los hallazgos histológicos hepáticos. El Ki67 es un biomarcador conocido para medir y controlar la proliferación celular. Métodos: Se midieron los niveles de expresión del parénquima hepático de Ki67 (clon, MIB‐1) por tinción inmunohistoquímica de las muestras de cinco donantes vivos y 35 pacientes con BA, para evaluar su valor predictivo de los resultados de la KP. Resultados: Los pacientes con BA incluían 13 sobrevivientes con hígado nativo ( native liver survivors, NLS), 17 no NLS y 5 pacientes que se sometieron inicialmente a LT. La proporción media de las áreas de expresión de Ki67 en donantes y pacientes con BA en KP fue de 0, 06% y 0, 99%, respectivamente. El análisis univariado identificó una alta proporción de áreas de Ki67, un alto número de células Ki67, un alto número de células Ki67 positivas (+)/leucocitos (LCA/CD45) + en KP como predictores significativos de una peor supervivencia del hígado nativo después de KP (cociente de riesgos instantáneos, hazard ratio, HR 9, 29, 3, 37 y 12, 17, respectivamente). La proporción de las áreas Ki67 fueron significativamente superiores en los pacientes sin NLS que en los pacientes con NLS ( P = 0, 001). Entre los pacientes sin hígado nativo, los niveles de Ki67 disminuyeron posteriormente de acuerdo con la presencia de una lesión hepática irreparable, tales como son los hígados con BA en LT (en KP versus en LT = 1, 29% versus 0.32%; P < 0, 001). Conclusión: Demostramos los datos clínicos y la evolución temporal de la expresión de Ki67 en los pacientes con BA. El alto nivel de expresión de Ki67 en KP puede ser un predictor importante para la supervivencia del hígado nativo después de KP.